Virtual Capacity Building for International Research Collaborations in Times of COVID-19 and #Flygskam - Richter, Isabel; Gabe-Thomas, Elizabeth; Maharja, Carya; Nguyen, Thu Ha; Van Nguyen, Quyen; Praptiwi, Radisti; Pahl, Sabine (Frontiers in Communication, 2021)
In the wake of the current global pandemic, international travel is restricted. This poses substantial challenges for research relationships aiming to build capacity and foster co-creation to achieve the Sustainable Development Goals, where global collaboration and communication is paramount. This is especially challenging when it comes to interactive dialogues that go beyond the typical one-way structure of online learning. Considerations on structural, technical and behavioural levels is needed to not only deal with these challenges but rather to take advantage of the new situation. This commentary outlines the lessons learned from an internationally operating project, co-developed to cope with travel restrictions. We discuss implications for future reduction of international travel to reduce carbon in the context of climate change.